Analisis Penerapan Good Corporate Governance dalam Kaitannya dengan Kinerja Karyawan - Siska Nur Oktavia; Rosdiana, Yuni (Bandung Conference Series: Accountancy, 2024)
Abstract. Employee performance is a form of an employee's success in achieving the strategic goals that have been set with the expected behavior. One of the factors that can affect employee performance is the implementation of good corporate governance in the company with the principles of transparency, accountability. responsibility, independence, and fairness. The implementation of Good Corporate Governance (GCG) is a form of implementing the company's control and management process that contains policies and regulates the relationships and responsibilities between employees, creditors and stakeholders in order to realize the company's goals. This research aims to determine the implementation of Good Corporate Governance at the Prodia Bandung Clinical Laboratory, to determine the performance of Prodia Clinical Laboratory employees Bandung and to find out the relationship between the implementation of Good Corporate Governance on the performance of Prodia Bandung Clinical Laboratory employees. This research uses a descriptive analysis research method using primary data sources through distributing questionnaires. The respondent in this study was the Prodia clinical lab manager with 10 employees. The data analysis technique uses descriptive statistical tests. The research results show, among other things: first, the implementation of Good Corporate Governance at the Prodia Bandung Clinical Laboratory in the total score of respondents' answers regarding Good Corporate Governance of 455. Second, the performance of Prodia Bandung Clinical Laboratory employees is the total score of respondents' answers of 419. Third, the implementation of Good Corporate Governance is related to the performance of Prodia Bandung Clinical Laboratory employees. This can be seen from the good perception of employees regarding the implementation of Good Corporate Governance at the Prodia Clinical Lab company. Abstrak. Kinerja karyawan adalah bentuk keberhasilan seorang karyawan dalam mencapai tujuan strategis yang telah ditetapkan dengan perilaku yang diharapkan. Salah satu faktor yang dapat mempengaruhi kinerja karyawan adalah penerapan Good Corporate Governance di dalam perusahaan dengan prinsip transparansi, akuntabilitas, responsibilitas, independensi, serta kewajiban dan kesetaraan. Penerapan Good Corporate Governance (GCG) adalah sebuah bentuk pelaksanaan proses pengendalian dan pengelolaan perusahaan yang berisi kebijakan serta mengatur hubungan dan tanggung jawab antara karyawan, manajer serta para pemangku kepentingan guna mewujudkan tujuan perusahaan. Penelitian ini bertujuan untuk mengetahui penerapan Good Corporate Governance pada Laboratorium Klinik Prodia Bandung, untuk mengetahui kinerja karyawan Laboratorium Klinik Prodia Bandung dan untuk mengetahui keterkaitan penerapan Good Corporate Governance pada kinerja karyawan Laboratorium Klinik Prodia Bandung. Penelitian ini menggunakan metode penelitian deskriptif analisis dengan sumber data primer melalui penyebaran kuesioner. Responden pada penelitian ini adalah manager laboratorium klinik Prodia dengan 10 karyawan. Teknik analisis data menggunakan uji deskriptif variabel. Hasil penelitian menunjukkan bahwa penerapan Good Corporate Governance pada Laboratorium Klinik Prodia Bandung termasuk pada kategori sangat baik. Kinerja karyawan Laboratorium Klinik Prodia Bandung termasuk pada kategori baik. Penerapan Good Corporate Governance memiliki keterkaitan dengan kinerja karyawan Laboratorium Klinik Prodia Bandung, dimana penerapan Good Corporate Governance nya sudah sangat baik dan kinerja karyawannya juga sangat baik pada Laboratorium Klinik Prodia.